OWNERSHIP, TAX AGGRESSIVENESS, DAN AUDIT QUALITY TERHADAP MANAJEMEN LABA - Aries Jonathan; Rehania Rachmayanti (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to determine whether there is an effect of ownership, tax aggressiveness and audit quality on earnings management in the company. In this study to test the consistency the result of each independent variable on dependent variable based on journals that have been researched previously. The companies used as samples in this study are non-financial companies that are listed in Indonesian stock exchange (IDX) from year 2018 until year 2020. There are 131 companies in Indonesia uses a purposive sampling method. Earnings management using discrectionary accruals which are calculated using modified jones model. Managerial ownership, Institutional ownership, foreign ownership, tax aggressiveness, firm financial leverage are measured using ratio’s scale. The age of company uses logarithms in its measurement. And audit quality use dummy variable. The result of this study shows that foreign ownership has effect on earnings management which means foreign company doesn’t have the financial resources, knowledge and corporate governance expertise which makes it difficult to obtain information. Meanwhile managerial ownership, institutional ownership, tax aggressiveness, firm financial leverage, firm age, and audit quality have no effect on earnings management.